The Effect Of The Effectiveness Of Accurate Accounting Software On The Accuracy Of The Company's Income Perspective (Case Study at PT. Nusapala Group) - Nadia Putri Asha (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
All companies want to demonstrate the best company performance. Company performance can be seen from the company's financial statements, especially on information about income. One of the efforts in trying to minimize errors in inputting income is using an Accounting Information System. The Accounting Information System is the most prominent part that is generated by the company. Researchers propose that income is net income which represents the amount of money from the company's revenue that has been adjusted for costs and additional income in the period. Researchers scrutinize the Accounting Information System as an important factor in calculating company income. The purpose of this study was to find out whether there is a change in the effect of the effectiveness of the Accurate Accounting Software on the accuracy of the company income perspective (case study at PT Nusapala Group). Respondents in this research amounted to 33 respondents. The data analysis technique used in this study uses simple linear regression analysis using SPSS statistical software version 25. The results of the research obtained on the effect of the effectiveness of the Accurate Accounting Software on the accuracy of the company income perspective (case study at PT Nusapala Group) that there is an R Square value of 0.504 which basically means that the contribution of accurate (X) influences income (Y) by 50.4% While the remaining 49.6% is influenced by other factors not known to researchers, from these results reveal that there is a significant positive effect between the Effectiveness of Accounting Information Systems and Company Income.